Community Service at Galerie Kirana On-Line Shop: Pengabdian kepada Masyarakat pada Galerie Kirana On-Line Shop - Veronika Nugraheni Sri Lestari; Reza Andriansyah; Nurmawati, Nurmawati; Subekti, Subekti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Online shopping has now become a modern trend that is enjoyed by most people, because it is able to attract and tempt every community, especially women. Because shopping cannot be separated from women, there are almost no women who do not like shopping. One of the media that is often used by online business people is Instagram social media. "GALERIE_KIRANA" is a real proof of an online shop engaged in women's fashion by utilising Instagram media as a liaison between sellers and buyers to conduct buying and selling transactions through online. The superior product of "GALERIE_KIRANA" is in the field of women fashion, especially Muslim clothing by covering various ages ranging from children, teenagers, to adults.This research uses the method of interviews and direct observation in the field, namely at the kirana e gallery to obtain data and information supporting the research, in addition to verifying information online at the kirana online shop